The multiple intelligences and their influence in the teaching-learning process of the english language with students of 1st, 2nd and 3rd years of high-school curriculum at “Trcn. Lauro Guerrero” militaryhigh-school of Loja city. Period 2009-2010 - ALBERCA ABAD, ERIKA CRISTINA (2010)
The present investigation is about “THE MULTIPLE INTELLIGENCES AND THEIR INFLUENCE IN THE TEACHING-LEARNING PROCESS OF THE ENGLISH LANGUAGE WITH STUDENTS OF 1ST, 2ND AND 3RD YEARS OF HIGH SCHOOL CURRICULUM AT “TCRN. LAURO GUERRERO” MILITARY HIGH SCHOOL OF LOJA CITY. PERIOD 2009-2010”, with the purpose to know and demonstrate the influence of the multiple intelligences in the teaching-learning process of English language. In this research work we used the scientific method, to do a logic explanation. As particular methods we used the descriptive, the analytical-sintethic and explicative one, finally we used the descriptive method that helped us with the identification and precisied delimitation, formulation of the hypothesis, recollection, organization and interpretation of the data. After analyzing the obtained results we deny the first hypothesis because we have proved that teachers take into account the multiple intelligences in the teaching-learning process, and we deny the second hypothesis too which mention that the techniques applied by teachers are not in relation to the multiple intelligences. Finally, we established some conclusions which are: the multiple intelligences are took into account in the teaching-learning process of the English language by teachers. Most of the teachers and students define the multiple intelligences as the style to learn, considering that they’re an essential instrument for education. The teachers know about multiple intelligences techniques but they don’t apply the corresponding ones to each intelligence so, they don’t use the different activities to develop meaningfully overall intelligences.